Education Responsibility Protection Environmental For Students: Duties, Requirements And Necessity - Luong, Pham Van; Van, Vu Hong (The journal of contemporary issues in business and government, 2021)
Currently, the living environment is heavily polluted, largely due to the destruction of humans. With regard to environmental pollution, the responsibilities of each Vietnamese citizen are the same. Any citizen needs to seriously comply with state regulations, raise their own awareness to contribute to preserving and protecting the environment. However, for many years, the awareness of environmental protection of students is attached and the work of educating the awareness of environmental protection in universities has not been paid attention. In order to have an accurate basis for assessing the awareness, responsibility of environmental protection and the importance of educating about environmental protection responsibility among students, the group surveyed 1,500 students, 120 lecturers, 20 organizing unions and associations in universities. Survey results showed that, education on environmental protection responsibility is very necessary; that is a requirement and a task that needs to be done immediately to raise students’ awareness in protecting the environment.